Pengaruh Model Pembelajaran Probing-Prompting Berbasis Etnomatematika Terhadap Prestasi Belajar Matematika Siswa - Maure, Osniman Paulina; Jenahut, Kondradus Silvester (Math Educa Journal, 2021)
One of the reasons for the low student achievement in mathematics is that the mathematics learning process carried out by the teacher tends to be theoretical and less contextual. Mathematics learning needs to be linked to student culture so that there is no gap between mathematics in everyday life and at school. Thus, it is necessary to apply a mathematics learning model based on ethno-mathematics. This study aims to determine the effect of the ethnomatematic based probing-prompting learning model on students' mathematics learning achievement. This type of research is quantitative research with pre-experimental methods and one-group pretest-posttest design. The sample of this research is class VIII A SMPK St. Yoseph Naikoten Kupang, totaling 24 people. The pretest and posttest values as research data were analyzed using the SPSS version 22 program. Based on the results of data analysis, thitung (39,594)> ttabel (2,069)  with an error rate of 0.05, which means accept Ha or the ethnomatematic based probing-prompting learning model has an influence which is significant towards the mathematics learning achievement of students class VIII SMPK  St. Yoseph Naikoten Kupang.